Existence and Nonuniqueness of Solutions to a Robin Boundary Problem for Semilinear Elliptic Equations (Journal of Partial Differential Equations, 2020)
Sufficient conditions for existence and nonuniqueness of radially symmetric solutions to the Robin boundary problem of the form Δu + a(||x||)|u|^{-p} = 0 \qquad in B ⊂ R^N \frac{∂u}{∂n} + λu = -α \qquad on ∂B are obtained.
Keywords: Robin boundary problem; positive solution; negative solution; nonuniqueness